2010
DOI: 10.4103/0970-2113.71967
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary alveolar microlithiasis with calcified pleural plaques

Abstract: Pulmonary alveolar microlithiasis (PAM) is a rare disease. Herein we report a case of pulmonary alveolar microlithiasis who was suspected to have the disease on chest X-ray and was confirmed on high resolution CT and transbronchial lung biopsy. These investigations showed characteristic features of pulmonary alveolar microlithiasis with diffuse interstitial pulmonary fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…7 Our case, however, showed a normal pattern of pulmonary function studies after re-expansion of the lung.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…7 Our case, however, showed a normal pattern of pulmonary function studies after re-expansion of the lung.…”
Section: Discussionmentioning
confidence: 64%
“…7 In 1918, Harbitz provided an accurate autopsy of a second case but it was Puhr in 1933 who named the disease mikrolithiasis alveolaris pulmonum. 8,9 A review of 576 published cases showed that there was no gender predominance and the ages of affected patients ranged from newborn to those in their ninth decade of life .…”
Section: Discussionmentioning
confidence: 97%
“…Although the radiological findings are diagnostic, many cases are mistaken for miliary tuberculosis, silicosis, berylliosis, sarcoidosis, haemosiderosis, fungal infections and carcinomatosis [8]. Radiologically, extensive micronodular opacities are seen in the basal and middle regions of both lungs in PAM.…”
Section: Discussionmentioning
confidence: 99%
“…Apical bullae can also be detected by chest X-ray or CT scans. Multiple calcified pleural plaques [49] and extensive interstitial fibrosis with traction bronchiectasis are observed rarely in our series [45].…”
Section: Investigationsmentioning
confidence: 98%